2013
DOI: 10.1164/rccm.201302-0342oc
|View full text |Cite
|
Sign up to set email alerts
|

Histone 3.3 Participates in a Self-Sustaining Cascade of Apoptosis That Contributes to the Progression of Chronic Obstructive Pulmonary Disease

Abstract: Rationale: Shifts in the gene expression of nuclear protein in chronic obstructive pulmonary disease (COPD), a progressive disease that is characterized by extensive lung inflammation and apoptosis, are common; however, the extent of the elevation of the core histones, which are the major components of nuclear proteins and their consequences in COPD, has not been characterized, which is important because extracellular histones are cytotoxic to endothelial and airway epithelial cells. Objectives: To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 49 publications
5
50
1
Order By: Relevance
“…In this study, we determined the novel histone acetylation and methylation marks in histones H3 and H4 caused by CS exposure in vitro and in vivo due to its involvement in DNA damage/repair, pro-inflammatory gene activation, genomic instability and cellular senescence in a site-specific manner 4549, 61, 62 . A recent study showed that extracellular, degradation-resistant, hyperacetylated histone H3.3 was elevated in lung of patients with COPD 31 . We and others have shown that human lung epithelial cells and mouse lung exposed to cigarette smoke causes histones H3 and H4 modifications limited to specific residues (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we determined the novel histone acetylation and methylation marks in histones H3 and H4 caused by CS exposure in vitro and in vivo due to its involvement in DNA damage/repair, pro-inflammatory gene activation, genomic instability and cellular senescence in a site-specific manner 4549, 61, 62 . A recent study showed that extracellular, degradation-resistant, hyperacetylated histone H3.3 was elevated in lung of patients with COPD 31 . We and others have shown that human lung epithelial cells and mouse lung exposed to cigarette smoke causes histones H3 and H4 modifications limited to specific residues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chromatin forms the extracellular trap protein components in neutrophils, particularly histones, which cause host cell cytotoxicity leading to the destruction of lung tissue 29 . It has been shown that circulating histones are mediators of trauma-associated lung injury 30 and are involved in apoptosis in lung cells 31 . Due to lack of evidence on the role of histone modifications in the pathogenesis of chronic lung diseases 13 , there is a need to study site-specific histone modifications using the rapidly growing mass spectrometry (MS) field.…”
Section: Introductionmentioning
confidence: 99%
“…The methods for label-free proteomics (GeLC-MS/MS) analysis were as previously described (42), except that the nanoelectrospray ionization (ESI) tandem MS was performed with a Q Exactive Orbitrap mass spectrometer (Thermo Scientific). ESI was delivered with a stainless steel emitter (30-µM inside diameter, 40-mm length, Thermo Scientific) at a spray voltage of −1800 V. MS/MS fragmentation was performed on the five most abundant ions on each spectrum using collision-induced dissociation with dynamic exclusion (excluded for 10.0 s after one spectrum), with automatic switching between MS and MS/MS modes.…”
Section: Methodsmentioning
confidence: 99%
“…Extracted proteins in radioimmune precipitation assay buffer from pooled xenograft tumors stably transfected with TRPM2-L (n ϭ 5) or TRPM2-S (n ϭ 5) and harvested at 6 weeks after cell injection were processed for GeLC-MS/MS analysis as described previously (50). Briefly, electrospray ionization tandem MS was performed using a Bruker HCT Ultra ion trap mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%